Seperation of bioactive compounds from Haemolymph of scarab beetle Scarabaeus sacer (Coleoptera: Scarabaeidae) by GC-MS and determination of its antimicrobial activity - doaa hassan abdelsalam; Nancy Taha Mohamed (International Journal of Applied Biology, 2021)
This study aimed to investigate the bioactive compounds in the haemolymph of scarab beetle Scarabaeus sacer by using the Gas chromatography–mass spectrometry (GS-MS) analysis. The identification of the bioactive compounds is based on peak area, retention time, molecular formula and molecular weight. There are 129 compounds are detected in the haemolymph of scarab beetle and 43 of them were reported to have a bioactivity. The most analyzed bioactive compounds are alcohols, steroids, fatty acids and terpenoids. The current study also test the antimicrobial activity of scarab beetle haemolymph against gram-negative bacteria (Escherichia coli, Enterobacter cloacae, gram-positive bacteria (Staphylococcus aureus, Bacillus subtilis), and fungi (Aspergillus fumigatus and Candida albicans). The haemolymph has highest antibacterial activity against gram negative bacteria Enterobacter cloacae, Escherichia coli respectively and against gram-positive bacteria Bacillus subtilis, Staphylococcus aureus respectively. No antifungal activity has been detected.